DFT Study on the Structures and Stability of BenSnn (n=1 – 5) and Be2nSnn (n=1 – 4) Clusters. - Fioressi, Silvina Ethel (2018)
The equilibrium geometries and stabilities of bimetallic BenSnn (n=1 – 5) and Be2nSnn (n=1 – 4) clusters were investigated through DFT calculations. Cluster geometries were optimized using DFT Monte Carlo simulated annealing and the energies ordered via single-point Quadratic Configuration Interaction (QCISD(T)) calculations evaluated at the optimized B3LYP geometries. Tridimensional highly symmetric structures were generally found as the most stable ones. They have much more in common with the beryllium silicides and germanides than with the carbides. In the larger clusters, a trend to form beryllium sub-structures capped by tin atoms was observed. The bonding between Be and Sn is largely covalent in character, which suggests that there exist the possibility of obtaining larger structures with novel properties and potential for the development of new materials.